Hardy’s Inequality on Time Scale - Ha, Nguyen Thu; Tuan, Le Anh (VNU Journal of Science: Mathematics - Physics, 2022)
This work is concerned with the Hardy inequalityon time scales. It finds the condition for the existence of a constant C such that where p is a fixed number satisfying .